Postoperative Opioid Consumption After Discharge: An Update From the Michigan Surgical Quality Collaborative Registry - Ashwin J. Kulkarni, BS; Vidhya Gunaseelan, MBA, MS, MHA; Chad M. Brummett, MD; Jennifer Waljee, MD, MPH, MSc; Michael Englesbe, MD; Mark C. Bicket, MD, PhD (Annals of Surgery Open)
Objective:. To evaluate opioid consumption for 21 procedures over 4 years from the Michigan Surgical Quality Collaborative (MSQC) registry and update post-discharge prescribing guidelines. Background:. Opioids remain a common treatment for postoperative pain of moderate-to-severe intensity not adequately addressed by nonopioid analgesics, but excessive prescribing correlates with increased usage. This analysis provides updates and compares patient-reported consumption in response to new guidelines. Methods:. We examined data from the MSQC registry for opioid-naive adult patients undergoing surgery between January 1, 2018, and October 31, 2021. The primary outcome was patient-reported opioid consumption in oxycodone 5 mg equivalents. Guidelines were anchored to the 75th percentile of consumption, updating previous guidelines from January 2020 based on data from January 1, 2018, to May 31, 2019. Results:. 39,493 opioid-naive surgical patients (average age 53.8 years [SD 16.4], 56.3% female, 19.1% non-White, 43.9% with public insurance) were included. Guidelines did not change for 7 of the 16 procedures including the most common procedures: minor hernia, laparoscopic cholecystectomy, laparoscopic appendectomy, and laparoscopic hysterectomy. Recommended prescribing ranges were lower for 9 procedures, with most (8) procedures having a reduction of 5 pills. Prescribing guidelines were developed for 5 new procedures. All procedures had upper-limit guidelines of 10 pills or less. Conclusions:. For most procedures, patient-reported opioid consumption decreased between 2018 and 2021 when compared to the period between 2018 and 2019. New guidelines were established for a dozen procedures to balance maximizing pain control with reducing harms from inappropriate prescribing.